Socioeconomic Determinants of Melanoma-Related Health Literacy and Attitudes Among College Students in China: A Population-Based Cross-Sectional Study - Wu, Tianhao; Wang, Xianggui; Zhao, Shuang; Xiao, Yi; Shen, Minxue; Han, Xi; Chen, Xiang; Su, Juan (Frontiers in Public Health, 2021)
Abstract Objectives: To investigate the association of gender, race, living region, and socioeconomic status(SES) with health literacy and attitudes towards nevi and melanoma in Chinese adolescents and to examine whether health literacy mediates the association of SES with attitudes. Study design: A multicenter cross-sectional study was conducted among newly enrolled college students. First-year students were recruited from five universities in different regions of China in 2018 using the cluster sampling method. The observers were blinded to the participants. Methods: Health literacy and attitude were measured using a previously validated tool(Nevus & Melanoma Health Literacy and Attitude Test). SES was measured by annual family income and parental highest educational level. Nonparametric test was used to examine the association of participants’ characteristics with health literacy and attitude. Two-level generalized linear model with logarithm link function and Gamma distribution was used individually for SES. The mediation effect model was used to examine the mediation effect of health literacy. Results: A total of 21086 questionnaires were completed by college students with a mean age of 18.0 ± 0.8 years. The mean scores of health literacy and attitudes were 9.83 ± 7.46 (maximum score: 28) and 16.98 ± 2.92 (maximum score: 20), respectively. Female, Han nationality, annual family income and parental educational levels were positively associated with health literacy and attitudes. Regional differences showed different effects on health literacy and attitude. A mediation model showed that literacy mediated the association of SES with attitudes towards nevi and melanoma. Health literacy mediated approximately 30–50% of the association of SES with attitudes. Conclusions: Melanoma-related health literacy among Chinese college students is generally insufficient and needs to be improved. Targeted and personalized health education for improving health literacy related to nevi and melanoma may improve the general population’s attitude and further promote health-related behavior to prevent and identify early-stage melanoma.